Pengaruh Brainwriting Berbasis Learning Management System (LMS) Terhadap Kemampuan Menulis Teks Eksposisi Siswa - Riza Aprilia Utama; Dedi Kuswandi; Saida Ulfa (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2021)
This research applied the brainwriting model learning Management System (LMS)-based on students in class X SMK Ma'arif Kota Batu to prove its effectiveness in learning to write exposition text. The study method used is experimental (Quasi-Experimental Design). The design applied was included in the non-equivalent control group design Posttest Only Control Group Design (POCGD) with a sample of 40 people divided into two groups. X-RPL as an experiment group and X-TO2 as a control group The research instrument applied a written test to measure learning outcomes write essays text exposition. Cronbach's alpha statistic test, Kolmogorov-Smirnov, Levene Statistics, independent t-test were used in this study. The results of the independent t-test statistic test by 2 assessors showed Sig. (2-tailed) of 0,000 with the conclusion that is rejected and is accepted. Thus it can be concluded that there is an influence by the implementation of the LMS-based brainwriting model on the ability to write essays text exposition.